RELATIONSHIP BETWEEN SATISFACTION AND PERCEIVED BODY IMAGE, BODY COMPOSITION AND PHYSICAL EXERCISE IN GYM USERS - Aguirre-Loaiza, Haney; Reyes, Sebastian; Ramos-Bermudez, Santiago; Bedoya, Diego A.; Franco, Alejandra M. [UNESP] (Revista Iberoamericana Psicologia Ejercicio & Deporte, 2017)
Some characteristic of the Bodily Composition (BC) and the Physical Exercise seem to be associated with the perception and the Body Image (IC). In a non-probabilistic sample of 247 users of gyms in the city of Armenia-Colombia, of both genders between 18 and 60 years of age (Mage=27.5, SD = 10.0), was studied the relationship between the IC, the BC and the physical exercise. From a Non-Experimental, association study, the model silhouettes IC was applied, also the anthropometric measurement was taken, including fat percentage according to Faulkners equation, the frequency and length of the physical information was measure through self-report. The results disclose that measures BC, weight, height, Body Mass Index, and body fat percentage are significantly correlated with the perception and satisfaction of the IC. Physical exercise does not yield significant correlations with the categories of perception and satisfaction of the IC. Gender differences are described, where women are significantly more dissatisfied. The results make clear the modulatory role of exercise in the IC and the relationship of objective measures of perception of the IC.
Keywords: Body Image; Exercise; Body Mass Index; Anthropometry. (PsycINFO - Thesaurus)